An extrusion-grade flame-retardant aliphatic polyketone composite material and a preparation method thereof
By adding halogen-free high-efficiency flame retardant and thermal stabilizer to the aliphatic polyketone composite material, the flame retardant performance, extrudability and heat resistance stability of the material are improved, and the problem of insufficient material performance in the existing technology is solved. , realizing applications in high-voltage components such as electric vehicles.
Patent Information
- Application Number
- CN202411504477.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-26
AI Technical Summary
In the prior art, the flame retardant properties, extrusionability and heat resistance of aliphatic polyketone composite materials are poor, and it is difficult to apply on high-pressure components such as electric vehicles.
By choosing a low -added amount of halogen -free and high -efficiency flame retardant and superior performance, the flame retardant and thermal resistance of the fatty polynalone resin are prepared to prepare the squeezed flame -retardant fatty polysone composite materials.
It achieves good extrusion processability, thermal stability and V0-level flame retardant performance of 0.4mm thickness of the composite material, simplifying the processing technology and reducing production costs.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to an extrusion-grade flame-retardant aliphatic polyketone composite material and a preparation method thereof. Background Art
[0002] Polyketone resin (POK) is a linear crystalline polymer obtained by alternating copolymerization of carbon monoxide and olefins (ethylene, propylene). The compact crystalline structure of polyketone resin gives the polymer excellent chemical resistance, impact resistance, abrasion resistance and high barrier properties. The presence of a large number of carbonyl groups in the main chain of polyketone resin provides the possibility of crosslinking, and this chemical reaction can be triggered by a variety of components, such as sizing agents for glass fibers, components of colorants, flame retardants, lubricants, toughening agents, nylon, acetal, etc., which may crosslink with polyketone resin. There are great challenges in the processing of POK materials. Adding POK materials to an extruder that has not been cleaned or staying in the extruder for a long time will cause crosslinking problems, resulting in the inability to extrude. Extrusion-grade flame-retardant aliphatic polyketone composite materials need to have good extrusion processability, processing thermal stability, toughness and flame retardancy before they can be used on high-voltage components such as busbars and copper busbars on electric vehicles.
[0003] In the prior art, diethyl aluminum hypophosphite and aluminum phosphite are usually added to aliphatic polyketone resins to modify and improve flame retardancy, and antioxidants and lubricants are added to improve the processing stability of the material. However, aliphatic polyketone resins have an extremely narrow processing temperature range and equipment residence time. If the temperature is slightly low, the material cannot melt; if the temperature is slightly high, the material stays for a long time, and it is easy to crosslink quickly and cannot be extruded smoothly. In addition, the crosslinking of polyketone resins is irreversible. After crosslinking, the fluidity of the overall mixed material is reduced, making it difficult to extrude, and even damaging the equipment. The addition of flame retardants further reduces the heat stability of the material, while the addition of conventional heat stabilizers does not improve the heat stability of the material much.
[0004] Therefore, there is an urgent need to solve the problems of poor flame retardancy, extrudability and heat stability of aliphatic polyketone composite materials in the prior art. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides an extrusion-grade flame-retardant aliphatic polyketone composite material and a preparation method thereof. The present invention selects a low-addition halogen-free high-efficiency flame retardant and a heat stabilizer with excellent performance to perform flame retardant and heat-resistant modification on an aliphatic polyketone resin material, thereby obtaining an extrusion-grade flame-retardant aliphatic polyketone composite material. The composite material has good extrusion processability and good thermal stability, and can reach V0 grade flame retardancy with a thickness of 0.4 mm. In addition, the composite material has a simple preparation process and low cost, and can be used in applications such as busbars, copper busbars, etc. on electric vehicles or industrial equipment.
[0006] The first aspect of the present invention provides an extrusion-grade flame-retardant aliphatic polyketone composite material, wherein the aliphatic polyketone composite material comprises the following components in parts by weight:
[0007] 85 to 95 parts of aliphatic polyketone resin;
[0008] Flame retardant 5~15 parts;
[0009] Heat stabilizer 0~1 part;
[0010] Antioxidant 0~1 part;
[0011] Lubricant 0~1 part;
[0012] Orange color powder 0~1 part;
[0013] The aliphatic polyketone resin is a mixture of a first aliphatic polyketone resin and a second aliphatic polyketone resin, the mass ratio of the first aliphatic polyketone resin to the second aliphatic polyketone resin is (8-9):1, and under the test conditions of 240°C and 2.16kg, the melt index of the first aliphatic polyketone resin is 3g / 10min-30g / 10min, the elongation at break is 280%-320%, and the notched impact strength is 200J / m-240J / m; under the test conditions of 240°C and 2.16kg, the melt index of the second aliphatic polyketone resin is 50g / 10min-70g / 10min, the elongation at break is 240%-260%, and the notched impact strength is 80J / m-100J / m.
[0014] As a preferred technical solution, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 1024, antioxidant 264, antioxidant 168, antioxidant 626, and antioxidant 9228.
[0015] As a preferred technical solution, the antioxidant is a combination of antioxidant 1010 and antioxidant 9228, and the mass ratio of the antioxidant 1010 to the antioxidant 9228 is (1-1): (1-5).
[0016] Antioxidant 1010 is a compound of the main antioxidant and the auxiliary antioxidant 9228, which has a synergistic effect and plays a better role in resisting thermal oxidative aging. The main antioxidant can react with the free radical R·ROO·, capture and remove active free radicals, convert them into hydroperoxides, interrupt the growth of active chains, eliminate the free radicals generated by the resin under high temperature, heat and light conditions, and achieve the purpose of protecting the polymer. The auxiliary antioxidant can decompose the hydroperoxides generated by the main antioxidant that still have a certain activity, so that it will no longer re-initiate the auto-oxidation reaction. In addition, the auxiliary antioxidant can inhibit and delay the generation of free radicals during the initiation process and passivate the metal ions remaining in the polymer.
[0017] As a preferred technical solution, the mass ratio between the antioxidant 1010 and the antioxidant 9228 is 1:1.
[0018] As a preferred technical solution, the lubricant is selected from at least one of N,N-ethylene bisstearamide, silicone, pentaerythritol stearate, montan wax, rice bran wax, silicone oil, polyethylene wax, and ethylene acrylic acid copolymer.
[0019] As a preferred technical solution, the lubricant is polyethylene wax.
[0020] Polyethylene wax has good demoulding properties, good compatibility with aliphatic polyketone resins, and a neutral pH value, and does not react with the active carbonyl groups on aliphatic polyketone resins.
[0021] As a preferred technical solution, the aliphatic polyketone (POK) resin is a linear crystalline polymer obtained by copolymerization of carbon monoxide, ethylene and propylene. The reaction formula of the aliphatic polyketone resin obtained by copolymerization of carbon monoxide, ethylene and propylene is as follows (I):
[0022] .
[0023] As a preferred technical solution, the first aliphatic polyketone resin and the second aliphatic polyketone resin can be the following brands of Korea Hyosung: M~230A, M330A, M630A, M630F, M620A, M710A, M730A, M730R, M930A, M410F~S, and JM033.
[0024] The melt index of the first aliphatic polyketone resin and the second aliphatic polyketone resin is obtained according to ASTM D1238, 240° C., 2.16 kg standard test.
[0025] The elongation at break of the first aliphatic polyketone resin and the second aliphatic polyketone resin is obtained by testing according to ASTM D638.
[0026] The notched impact strength of the first aliphatic polyketone resin and the second aliphatic polyketone resin is obtained by testing at 23° C. according to the standard test of ASTM D256.
[0027] As a preferred technical solution, the first aliphatic polyketone resin has a melt index of 6 g / 10 min, an elongation at break of 300%, and a notched impact strength of 220 J / m.
[0028] As a preferred technical solution, the first aliphatic polyketone resin may be M630F produced by Korea Hyosung.
[0029] As a preferred technical solution, the second aliphatic polyketone resin has a melt index of 60 g / 10 min, an elongation at break of 250%, and a notched impact strength of 98.1 J / m.
[0030] As a preferred technical solution, the second aliphatic polyketone resin may be M330A produced by Korea Hyosung.
[0031] The inventors found that the aliphatic polyketone resin is a mixture of a first aliphatic polyketone resin and a second aliphatic polyketone resin, and when the mass ratio between the first aliphatic polyketone resin and the second aliphatic polyketone resin is (8-9):1, the composite material has good toughness and processing fluidity, which facilitates the processing and extrusion of the composite material.
[0032] By adding propylene during the copolymerization of aliphatic polyketone resins, a ternary copolymer polyketone material with a lower melting point and easier processing can be obtained.
[0033] As a preferred technical solution, the flame retardant is selected from at least one of diisobutyl aluminum phosphite, diethyl aluminum phosphite, dihexyl aluminum phosphite, aluminum phosphite, melamine polyphosphate, magnesium hydroxide, aluminum hydroxide, antimony trioxide, and zinc borate, and the flame retardant particle diameter ranges from 1 mm to 3 mm.
[0034] As a preferred technical solution, the flame retardant is aluminum diisobutylphosphinate.
[0035] When the particle size of the flame retardant is small, the flame retardant efficiency is high, but the bulk density is low, which makes processing difficult. The inventors found that when the diameter of the flame retardant particles is 1mm~3mm, it has both good flame retardancy and good processability. Aluminum diisobutylphosphinate releases gaseous substances in the early stage of thermal decomposition, and forms more carbon layers in the later degradation process, which plays a role in heat insulation and oxygen isolation, and has good flame retardant properties.
[0036] As a preferred technical solution, the heat stabilizer is selected from at least one of potassium dihydrogen phosphate, sodium dihydrogen phosphate, triphenyl phosphate, zinc oxide, hydrotalcite, calcium oxide, calcium stearate, and calcium montanate.
[0037] As a preferred technical solution, the thermal stabilizer is hydrotalcite, and the particle size d50 of the hydrotalcite is 0.30-0.60 μm.
[0038] As a preferred technical solution, the hydrotalcite is Japan Kyowa Chemical hydrotalcite and / or Germany Clariant hydrotalcite, the Japan Kyowa Chemical hydrotalcite is selected from at least one of the brands MAGCELER 1, DHT 4A, DHT~4V, DHT~4C, DHT~4A~2, ALCAMIZER 1, ALCAMIZER 2, ALCAMIZER 5, ALCAMIZER CP, ALCAMIZER P93~2, ALCAMIZERPlus, ALCAMIZER WP, and ALCAMIZER P93, and the German Clariant hydrotalcite is Clariant Hycite 713.
[0039] As a preferred technical solution, the hydrotalcite is Clariant Hycite 713, and the particle size d50 is 0.30-0.60 μm.
[0040] Hydrotalcite is used as a heat stabilizer and acid absorber. The hydrotalcite used in the present invention has a small particle size, is well dispersed in the resin, and has a fast effect. In addition, it can avoid the appearance of granularity on the surface of extruded and injection molded parts. When the particles are large, it is easy to have a granular feeling on the extruded parts.
[0041] As a preferred technical solution, the orange toner is an azomethine complex with a particle size of 200-250 nm.
[0042] The inventors found that when the orange color powder is an azomethine complex with a particle size of 200-250 nm, it has good compatibility with the aliphatic polyketone composite material and can evenly dye the aliphatic polyketone composite material.
[0043] As a preferred technical solution, the orange color powder is selected from at least one of BASF Oracet orange220, BASF Oracet orange260, BASF Oracet Orange K2430, LANXESS 3G Orange, Clariant PV FAST Orange6RL, Clariant PV Fast Orange 6RL~LHC, Clariant PV FAST ORANGE H2GL, PV FAST ORANGEGRL, and HOSTASOL RED GG.
[0044] As a preferred technical solution, the orange toner is Clariant PV FAST Orange 6RL, which is an azomethine complex with a particle size of 221 nm.
[0045] The dye in the technical solution of the present invention is not suitable for acid dyes, which will react with a large number of carbonyl groups in the polymer chain to accelerate the cross-linking process of the material. The composite material in the present invention is used for high-voltage components. In electric vehicles, orange has become an important symbol color for distinguishing high-voltage components.
[0046] An extrusion-grade flame-retardant aliphatic polyketone composite material, wherein the aliphatic polyketone composite material comprises the following components in parts by weight:
[0047] 85 to 95 parts of aliphatic polyketone resin;
[0048] 5 to 15 parts of diisobutyl aluminum hypophosphite;
[0049] Hydrotalcite 0~1 part;
[0050] Antioxidant 0~1 part;
[0051] Lubricant 0~1 part;
[0052] Orange color powder 0~1 part;
[0053] The aliphatic polyketone resin is a mixture of a first aliphatic polyketone resin and a second aliphatic polyketone resin, the mass ratio of the first aliphatic polyketone resin to the second aliphatic polyketone resin is (8-9):1, and under the test conditions of 240°C and 2.16kg, the melt index of the first aliphatic polyketone resin is 3g / 10min-30g / 10min, the elongation at break is 280%-320%, and the notched impact strength is 200J / m-240J / m; under the test conditions of 240°C and 2.16kg, the melt index of the second aliphatic polyketone resin is 50g / 10min-70g / 10min, the elongation at break is 240%-260%, and the notched impact strength is 80J / m-100J / m.
[0054] The second aspect of the present invention provides a method for preparing the extrusion-grade flame-retardant aliphatic polyketone composite material, comprising at least the following steps:
[0055] The aliphatic polyketone resin is mixed with a flame retardant, a heat stabilizer, an antioxidant, a lubricant and an orange color powder, and then extruded to obtain an extrusion-grade flame-retardant aliphatic polyketone composite material.
[0056] As a preferred solution of the present invention, the extrusion is performed using a twin-screw extruder, wherein the screw aspect ratio of the twin-screw extruder is (36-40):1, the barrel temperature is 190°C-240°C, and the screw speed is 250rpm-350rpm.
[0057] Beneficial Effects
[0058] In the present invention, the flame retardant properties of the aliphatic polyketone composite material can be effectively improved by adding a low amount of flame retardant, so that the material reaches 0.4mm V0 level. By adding a suitable heat stabilizer in the overall material, the residence time of the chain composite material in the extrusion equipment is extended, so that the composite material has good processing stability, and the processing difficulty of the material is simplified. In addition, the material has good toughness and fluidity through the compounding of aliphatic polyketone resin, hydrotalcite and lubricant, so that the preparation process of the aliphatic polyketone composite material is simplified, and the production cost is reduced. The aliphatic polyketone composite material in the present invention can be used for applications such as busbars, copper busbars, etc. on electric vehicles or industrial equipment. DETAILED DESCRIPTION
[0059] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below. However, the following embodiments are only simple examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0060] The specific embodiment of the present invention provides an extrusion-grade flame-retardant aliphatic polyketone composite material, which comprises the following components in parts by weight:
[0061] 85 to 95 parts of aliphatic polyketone resin;
[0062] Flame retardant 5~15 parts;
[0063] Heat stabilizer 0~1 part;
[0064] Antioxidant 0~1 part;
[0065] Lubricant 0~1 part;
[0066] Orange color powder 0~1 part;
[0067] The aliphatic polyketone resin is a mixture of a first aliphatic polyketone resin and a second aliphatic polyketone resin, the mass ratio of the first aliphatic polyketone resin to the second aliphatic polyketone resin is (8-9):1, and under the test conditions of 240°C and 2.16kg, the melt index of the first aliphatic polyketone resin is 3g / 10min-30g / 10min, the elongation at break is 280%-320%, and the notched impact strength is 200J / m-240J / m; under the test conditions of 240°C and 2.16kg, the melt index of the second aliphatic polyketone resin is 50g / 10min-70g / 10min, the elongation at break is 240%-260%, and the notched impact strength is 80J / m-100J / m.
[0068] As a preferred technical solution, the extrusion-grade flame-retardant aliphatic polyketone composite material comprises the following components in parts by weight:
[0069] 85 to 95 parts of aliphatic polyketone resin;
[0070] The flame retardant is 5 to 15 parts of aluminum diisobutylphosphinate;
[0071] The heat stabilizer is 0 to 1 part of hydrotalcite;
[0072] Antioxidant 0~1 part;
[0073] Lubricant 0~1 part;
[0074] Orange color powder 0~1 part;
[0075] The aliphatic polyketone resin is a mixture of a first aliphatic polyketone resin and a second aliphatic polyketone resin, the mass ratio of the first aliphatic polyketone resin to the second aliphatic polyketone resin is (8-9):1, and under the test conditions of 240°C and 2.16kg, the melt index of the first aliphatic polyketone resin is 3g / 10min-30g / 10min, the elongation at break is 280%-320%, and the notched impact strength is 200J / m-240J / m; under the test conditions of 240°C and 2.16kg, the melt index of the second aliphatic polyketone resin is 50g / 10min-70g / 10min, the elongation at break is 240%-260%, and the notched impact strength is 80J / m-100J / m.
[0076] Among them, the weight of aliphatic polyketone resin can be 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts or 91 parts, etc., but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The weight of flame retardant can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts, etc., but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The weight of heat stabilizer can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 10 parts, etc., but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0077] The weight of the antioxidant can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 10 parts, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable. The weight of the lubricant can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1 part, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable.
[0078] As a preferred technical solution, the antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 1024, antioxidant 264, antioxidant 168, antioxidant 626, and antioxidant 9228.
[0079] As a preferred technical solution, the antioxidant is a combination of antioxidant 1010 and antioxidant 9228, and the mass ratio of the antioxidant 1010 to the antioxidant 9228 is (1-5): (1-5).
[0080] As a preferred technical solution, the mass ratio between the antioxidant 1010 and the antioxidant 9228 is 1:1.
[0081] As a preferred technical solution, the lubricant is selected from at least one of N,N-ethylene bisstearamide, silicone, pentaerythritol stearate, montan wax, rice bran wax, silicone oil, polyethylene wax, and ethylene acrylic acid copolymer.
[0082] As a preferred technical solution, the lubricant is polyethylene wax.
[0083] As a preferred technical solution, the aliphatic polyketone (POK) resin is a linear crystalline polymer obtained by copolymerization of carbon monoxide, ethylene and propylene. The reaction formula of the aliphatic polyketone resin obtained by copolymerization of carbon monoxide, ethylene and propylene is as follows (I):
[0084] .
[0085] As a preferred technical solution, the first aliphatic polyketone resin and the second aliphatic polyketone resin can be the following brands of Korea Hyosung: M~230A, M330A, M630A, M630F, M620A, M710A, M730A, M730R, M930A, M410F~S, and JM033.
[0086] The melt index of the first aliphatic polyketone resin and the second aliphatic polyketone resin is obtained according to ASTM D1238, 240° C., 2.16 kg standard test.
[0087] The elongation at break of the first aliphatic polyketone resin and the second aliphatic polyketone resin is obtained by testing according to ASTM D638.
[0088] The notched impact strength of the first aliphatic polyketone resin and the second aliphatic polyketone resin is obtained by testing at 23° C. according to the standard test of ASTM D256.
[0089] As a preferred technical solution, the first aliphatic polyketone resin has a melt index of 6 g / 10 min, an elongation at break of 300%, and a notched impact strength of 220 J / m.
[0090] As a preferred technical solution, the first aliphatic polyketone resin may be M630F produced by Korea Hyosung.
[0091] As a preferred technical solution, the second aliphatic polyketone resin has a melt index of 60 g / 10 min, an elongation at break of 250%, and a notched impact strength of 98.1 J / m.
[0092] As a preferred technical solution, the second aliphatic polyketone resin may be M330A produced by Korea Hyosung.
[0093] As a preferred technical solution, the flame retardant is selected from at least one of diisobutyl aluminum phosphite, diethyl aluminum phosphite, dihexyl aluminum phosphite, aluminum phosphite, melamine polyphosphate, magnesium hydroxide, aluminum hydroxide, antimony trioxide, and zinc borate, and the flame retardant particle diameter ranges from 1 mm to 3 mm.
[0094] As a preferred technical solution, the flame retardant is aluminum diisobutylphosphinate.
[0095] As a preferred technical solution, the thermal stabilizer is hydrotalcite, and the particle size d50 of the hydrotalcite is 0.30-0.60 μm.
[0096] As a preferred technical solution, the hydrotalcite is Japan Kyowa Chemical hydrotalcite and / or Germany Clariant hydrotalcite, the Japan Kyowa Chemical hydrotalcite is selected from at least one of the brands MAGCELER 1, DHT 4A, DHT~4V, DHT~4C, DHT~4A~2, ALCAMIZER 1, ALCAMIZER 2, ALCAMIZER 5, ALCAMIZER CP, ALCAMIZER P93~2, ALCAMIZERPlus, ALCAMIZER WP, and ALCAMIZER P93, and the German Clariant hydrotalcite is Clariant Hycite 713.
[0097] As a preferred technical solution, the hydrotalcite is Clariant Hycite 713, and the particle size d50 is 0.30-0.60 μm.
[0098] As a preferred technical solution, the orange toner is an azomethine complex with a particle size of 200-250 nm.
[0099] As a preferred technical solution, the orange color powder is selected from at least one of BASF Oracet orange220, BASF Oracet orange260, BASF Oracet Orange K2430, LANXESS 3G Orange, Clariant PV FAST Orange6RL, Clariant PV Fast Orange 6RL~LHC, Clariant PV FAST ORANGE H2GL, PV FAST ORANGEGRL, and HOSTASOL RED GG.
[0100] As a preferred technical solution, the orange toner is Clariant PV FAST Orange 6RL, which is an azomethine complex with a particle size of 221 nm.
[0101] As a preferred embodiment of the present invention, the screw aspect ratio of the twin-screw extruder is 36~40:1, for example, 36:1 or 40:1, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable; the barrel temperature is 190°C~240°C, for example, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C, and is not limited to the listed values, and other values not listed within the numerical range are equally applicable; the screw speed is 250rpm~350rpm, for example, 250rpm, 270rpm, 290rpm, 310rpm, 330rpm, or 350rpm, but is not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0102] The following are typical but non-limiting embodiments of the present invention:
[0103] Example
[0104] The formula materials used in Examples 1 to 3 and Comparative Examples 1 to 8 are shown in Table 1. The preparation methods of the extrusion grade flame retardant aliphatic polyketone composite materials in Examples 1 to 3 and Comparative Examples 1 to 8 are the same, which is the following preparation method:
[0105] (1) Weigh the raw materials according to the ratio and put them into a high-speed mixer for stirring for 20 minutes to obtain a premix;
[0106] (2) The premix obtained in step (1) is put into a twin-screw extruder for melt mixing, and extrusion granulation to obtain an aliphatic polyketone composite material, wherein the screw aspect ratio of the twin-screw extruder is 36:1, the barrel temperature is 230°C, 230°C, 220°C, 220°C, 220°C, 220°C, 220°C, 220°C, 220°C, the die temperature is 230°C, and the screw speed is 300 rpm.
[0107] Table 1: Table of materials used in comparative examples 1 to 8 and examples 1 to 3
[0108]
[0109] The flame retardant aluminum diisobutylphosphinate described in Table 1 was purchased from Hebei Xinxinyuan, and the particle diameter ranged from 1 mm to 3 mm.
[0110] The melt index of aliphatic polyketone resin Korea Hyosung POK M630F is 6g / 10min, the elongation at break is 300%, and the notched impact strength is 220J / m. The melt index is obtained according to the standard test of ASTM D1238, 240℃, 2.16kg, the notched impact strength is obtained according to the standard test of ASTM D256, tested at 23℃, and the elongation at break is obtained according to the standard test of ASTM D638.
[0111] The melt index of aliphatic polyketone resin Korea Hyosung POK M330A is 60g / 10min, the elongation at break is 250%, and the notched impact strength is 98.1J / m. The melt index is obtained according to the standard test of ASTM D1238, 240℃, 2.16kg, the notched impact strength is obtained according to the standard test of ASTM D256, tested at 23℃, and the elongation at break is obtained according to the standard test of ASTM D638.
[0112] The particle size d50 of Clariant Hycite 713 is 0.4 μm.
[0113] The aliphatic polyketone composite materials in Examples 1 to 3 and Comparative Examples 1 to 8 were tested by the following specific method:
[0114] The prepared plastic particles were dried in a blast oven at 60°C for 4 hours and then injected into standard ISO specimens using a plastic injection molding machine. The injection molding temperature was 220~240°C. The injection-molded specimens were immediately placed in a glass dryer and left at room temperature for at least 24 hours before performance testing. The tensile strength and elongation at break were tested using the "Test Method for Tensile Properties of Plastics" (ISO 527~2), and the melt mass flow rate (MFR) was tested using the "Plastics. Determination of Melt Mass Flow Rate (MFR) and Melt Volume Flow Rate (MVR) of Thermoplastics. Standard Method" (ISO 1133). The test conditions were 240°C / 2.16kg. The flame retardant properties were tested according to the 0.4mm thick vertical burning grade in the test standard "UL94". The evaluation method of heat residence time adopts the more common method in the current industry: use the injection molding machine to store materials according to the processing temperature conditions of 240~235~230~225~220℃. After the storage is completed, start the timing. After staying for 4 minutes, start to empty the resin in the barrel and check whether the discharged material strips show a tendency to cross-link (the surface of the material strips is rough, lacks gloss, and the fluidity is deteriorated). Repeat the heat residence test with an increase of 0.5 minutes until cross-linking is found during injection. The previous time is recorded as the longest thermal stability time. The longest thermal stability time can reflect the thermal stability of the material. It can be converted by the formula (8×screw diameter / metering distance-buffer distance)×number of repetitions to estimate the longest residence time of the aliphatic polyketone composite material in the barrel of the extrusion equipment. The estimated longest residence time is recorded as the thermal residence time.
[0115] The test results of the aliphatic polyketone composite materials in Examples 1 to 3 and Comparative Examples 1 to 8 are shown in Table 2.
[0116] Table 2: Material test results in Examples 1 to 3 and Comparative Examples 1 to 8
[0117]
[0118] It can be seen from the test results that the present invention can effectively improve the fluidity, toughness and thermal stability of the aliphatic polyketone composite material by adding suitable flame retardants, heat stabilizers, lubricants and orange toners, so that the elongation at break of the material reaches more than 20%, and its thermal residence time is more than 9 minutes. By using low-added organic phosphonates, neutral lubricants and toners, conflicts with a large number of active carbonyl bonds in the material molecular chain are avoided, and efficient heat stabilizers are added to react with active groups generated during the processing, which effectively improves the thermal stability of the composite material.
[0119] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An extrusion grade flame retardant aliphatic polyketone composite material, characterized in that: The aliphatic polyketone composite material comprises the following components by weight: 91.5 parts of aliphatic polyketone resin; Flame retardant 7 parts; 0.5 parts of heat stabilizer; 0.5 parts of antioxidant; 0.25 parts of lubricant; 0.25 parts of orange color powder; The aliphatic polyketone resin is a mixture of a first aliphatic polyketone resin and a second aliphatic polyketone resin, wherein the mass ratio of the first aliphatic polyketone resin to the second aliphatic polyketone resin is (8-9):1, and under the test conditions of 240° C. and 2.16 kg, the first aliphatic polyketone resin has a melt index of 6 g / 10 min, an elongation at break of 300%, and a notched impact strength of 220 J / m, and under the test conditions of 240° C. and 2.16 kg, the second aliphatic polyketone resin has a melt index of The invention discloses a novel ...
2. The extrusion-grade flame-retardant aliphatic polyketone composite material according to claim 1, wherein the aliphatic polyketone resin is a linear crystalline high molecular polymer obtained by copolymerization of carbon monoxide, ethylene and propylene, and the reaction formula of the aliphatic polyketone resin obtained by copolymerization of carbon monoxide, ethylene and propylene is as follows (I): 。 3. A method for preparing the extrusion-grade flame-retardant aliphatic polyketone composite material according to any one of claims 1 to 2, characterized in that: At least the following steps are included: The aliphatic polyketone resin is mixed with a flame retardant, a heat stabilizer, an antioxidant, a lubricant and an orange color powder, and then extruded to obtain an extrusion-grade flame-retardant aliphatic polyketone composite material.
4. The method for preparing the extrusion-grade flame-retardant aliphatic polyketone composite material according to claim 3, characterized in that: The extrusion is performed using a twin-screw extruder, wherein the screw length-diameter ratio of the twin-screw extruder is (36-40):1, the barrel temperature is 190°C-240°C, and the screw speed is 250rpm-350rpm.
Citation Information
Patent Citations
Polyketone moulding compounds with improved properties, moulded articles produced therefrom and also method for the production thereof
CN106905684A